2015
DOI: 10.1021/acschembio.5b00592
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Selection of Peptide–Peptoid Hybrids Specific for Lung Cancer Compared to Normal Lung Epithelial Cells

Abstract: To develop widely-applicable diagnostic and potentially therapeutic approaches overcoming protein heterogeneity in human cancer, we have developed a technology to unbiasedly select high specificity compound(s) that bind any bio-molecule (e.g., proteins, lipids, carbohydrates) presented on the cancer cell surface but not on normal cells. We utilized a peptidomimetic based on-bead two-color (OBTC) combinatorial cell screen that can detect differences between two cell surfaces at high accuracy by looking for bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 46 publications
5
37
0
Order By: Relevance
“…All the dimers were synthesized using the complete on-bead synthesis protocol described in our previous reports. 10,27 Briefly, peptide portions were synthesized using the standard Fmoc synthesis approach, and peptoid residues were coupled using the standard microwave-assisted peptoid synthesis protocol 28, 29 All compounds were purified using semi-preparative HPLC. Purity was confirmed by analytical HPLC, and synthesis was confirmed by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (Supplementary Figure S2–S9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the dimers were synthesized using the complete on-bead synthesis protocol described in our previous reports. 10,27 Briefly, peptide portions were synthesized using the standard Fmoc synthesis approach, and peptoid residues were coupled using the standard microwave-assisted peptoid synthesis protocol 28, 29 All compounds were purified using semi-preparative HPLC. Purity was confirmed by analytical HPLC, and synthesis was confirmed by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (Supplementary Figure S2–S9).…”
Section: Resultsmentioning
confidence: 99%
“…9 PPS1 was identified via an unbiased selection approach using our unique on-bead two-color cell screen (OBTC), which is capable of recognizing the difference between two cell surfaces. 10 In our previous study, we targeted red stained HCC4017 lung cancer cells in the presence of green stained HBEC30KT normal bronchial epithelial cells derived from the same patient. We mixed these two cell types in a 1:1 ratio and exposed to one-bead one-compound peptide-peptoid hybrid library synthesized on tentagel beads.…”
Section: Introductionmentioning
confidence: 99%
“…It is found in the inner layer of normal cell membranes, but in cancerous and tumor endothelial cells it is reported to be transferred (i.e., flipped) to the outer layer of the lipid membrane, thereby providing a promising cancer biomarker target with increased specificity over that of normal cells 4, 7–12 . More importantly, this PS flipping in cancer and tumor endothelial cells in the tumor microenvironment is universal, indicating that PS targeted drugs may have efficacy as common anticancer drugs 7, 8, 1317 .…”
Section: Introductionmentioning
confidence: 98%
“…PPS1 displayed specific binding towards lipids that had an overall negative charge that were present on cancer cells, but not normal cells 14, 17 . The simple dimeric version of PPS1, PPS1D1 displayed cancer cell killing activity, but had no effect on normal cells 13 . Our recently reported alanine/sarcosine scan studies identified two positively charged residues at the second and third position and four C-terminal hydrophobic residues that composed the minimum pharmacophore 15 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation